(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This paper details the design, development, and evaluation of an electronic monitoring device for detecting termite activity in real time. The device employs a combination of moisture, vibration, and temperature sensors to gather data indicative of termite presence. Field trials conducted in both urban and rural settings demonstrated the device’s accuracy (over 90%) in identifying termite activity. This research underscores the potential of electronic monitoring systems to enhance termite management practices, contributing to more effective and environmentally friendly pest control strategies